Pengaruh Gaya Hidup terhadap Consumer Ethnocentrism (Studi pada Mahasiswa di Yogyakarta) - Haryono, Sigit (BISMA (Bisnis dan Manajemen), 2018)
This study aims to explain relationship fashion consciousness and leadership, as part of lifestyle, toward consumer ethnocentrism. Research population is student in Yogyakarta. Type of the research is explanatory and data collection use questionair. Research instrument lifestyle used Kucukemiroglu and instrument consumer ethnocentrism used Shimp dan Sharma. Result of the study is fashion consciousness and leadership have relationship with consumer ethnocentrism.This study also found that level consumer ethnocentrism is very high.